Crafting the news. Issue 2 (3rd April 2017) - Strawser, Michael G.
Abstract : Courses: This activity could be used in a basic public-speaking course to demonstrate messaging and the development of the three pillars of public speaking: content, organization, and delivery. In a basic communication course, this activity would help illustrate the process of communication (sender, receiver, feedback, channel, etc.). A mass communication class can use this activity to discuss the power of news outlets and social media while digging into mass communication theory (agenda setting, computer mediated communication, framing, etc.). Objectives: Through collaboration with teammates, small groups of students will develop a three- to five-minute news segment that will be posted on YouTube upon completion. Through social-media distribution of the YouTube link, this news clip must attract a certain number (the final number can be determined by the instructor) of viewers in a specified time limit. Student participants will be responsible for identifying valid sources and compiling credible information pertaining to their news topic while also illustrating effective competency in speech content, organization, and delivery by preparing a presentation that is trustworthy and interesting, concise and clear, and presented with energy and charisma while conducting proper vocal and body delivery techniques. The "big question": can the group create a credible, clear, concise, coherent news broadcast and distribute the finished project to a social-media outlet in the hopes of gaining a certain number of viewers?